Empowering the Female City Manager to Succeed: What Role Does Mentoring Play in the Personal Development and Preparation of Women for this Leadership Position?. (1st March 2021) - French, P. Edward; Eskridge, Robert D.
Abstract: How does mentoring impact the personal work‐related attitudes of female city managers in the United States? Data from a survey of female city managers from cities of 5, 000 people or more show that mentoring relationships often have a positive impact on the participant's self‐confidence and preparation for her position in terms of understanding work processes, responsibilities, and relationships. Mentoring is especially important to females who are employed in their first city manager position as survey data indicate that nonmentored female managers perceive more personal challenges with several activities including general administrative duties, developing and managing the budget and policies, and preparing and implementing a strategic plan, as well as a healthy balance of their work and personal life.